Polymeric nanoparticles encapsulating novel TLR7/8 agonists as immunostimulatory adjuvants for enhanced cancer immunotherapy. (May 2018) - Kim, Hyunjoon; Niu, Lin; Larson, Peter; Kucaba, Tamara A.; Murphy, Katherine A.; James, Britnie R.; Ferguson, David M.; Griffith, Thomas S.; Panyam, Jayanth
Abstract: Cytotoxic T lymphocytes (CTLs) play a major role in cancer immunotherapy because of their ability to directly kill tumor cells and secrete tumor suppressive cytokines. Anticancer vaccines aim to provoke tumor-specific CTL responses, which require activation of antigen presenting cells (APCs) including dendritic cells (DCs) and macrophages. Therefore, a potent immunostimulatory adjuvant capable of activating APCs is an essential component of anticancer vaccines. In this study, we introduce novel TLR 7/8 bi-specific agonists that significantly enhance cytokine secretion compared to TLR7 mono-selective compounds. Encapsulation of these TLR 7/8 agonists in poly(lactide- co -glycolide) (PLGA) nanoparticles increased the co-stimulatory molecule expression and antigen presentation via MHC I by DCs compared to the soluble agonist. When administered subcutaneously, these nanoparticles migrated to draining lymph node and triggered DC activation and expansion. This lead to expansion of antigen-specific CD8 T cells and enhanced CTL response, which resulted in significant prophylactic and therapeutic efficacy in melanoma, bladder and renal cell carcinoma tumor models. Importantly, our studies demonstrate significant reductions in systemic metastasis with the nanoparticle vaccine. Our results suggest novel TLR 7/8 agonist-encapsulated nanoparticles are potent immunostimulatory adjuvants for cancer immunotherapy.